2010
DOI: 10.1002/ps.1984
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐resistance and possible mechanisms of chlorpyrifos resistance in Laodelphax striatellus (Fallén)

Abstract: The high cross-resistance to the organophosphate dichlorvos in the chlorpyrifos-resistant strain suggests that other non-organophosphate insecticides would be necessary to counter resistance, should it arise in the field. Enhanced activities of carboxylesterase and the acetylcholinesterase insensitivity appear to be important mechanisms for chlorpyrifos resistance in L. striatellus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 16 publications
1
38
0
Order By: Relevance
“…For example, resistance to pesticides in insects is frequently achieved by overexpression of endogenous CEs that can inactivate these compounds [85-88]. Potentially therefore, combining a selective inhibitor of this enzyme with the pesticide, should result in increased toxicity of the latter to the organism.…”
Section: Expert Opinionmentioning
confidence: 99%
“…For example, resistance to pesticides in insects is frequently achieved by overexpression of endogenous CEs that can inactivate these compounds [85-88]. Potentially therefore, combining a selective inhibitor of this enzyme with the pesticide, should result in increased toxicity of the latter to the organism.…”
Section: Expert Opinionmentioning
confidence: 99%
“…Resistance to chlorpyrifos has been reported in many insect species including Tetranychus evansi (581.5‐fold), Chrysoperla carnea (37‐fold), Chilo suppressalis (11.4–36.9‐fold), Choristoneura rosaceana (24.96‐fold), Helicoverpa armigera (2.6–24‐fold), Spodoptera litura (15.1–55.1‐fold) and Bemisia tabaci (21.8‐fold), with different mechanisms reported, such as mutation and amplification of the acetylcholinesterase‐1 ( T. evansi ), target‐site insensitivity ( C. suppressalis ) and metabolic mechanisms due to enhanced cytochrome P450, esterase and glutathione‐ S ‐transferase activities ( C. rosaceana , C. carnea , H. armigera , S. litura and B. tabaci ). Previous studies on laboratory‐selected populations showed that L. striatellus could develop a high level of resistance to chlorpyrifos (188.55‐fold), and enhanced activity of carboxylesterase was suggested as a mechanism of the resistance . Further study reported that Ls.CarE1 overexpression might be involved in chlorpyrifos resistance .…”
Section: Introductionmentioning
confidence: 97%
“…The most common management strategy to control these planthoppers is chemical treatments. However, this inevitably leads to the development of insecticide resistance, insect resurgence, and serious environmental pollution [1][5]. Alternative control strategies must be developed.…”
Section: Introductionmentioning
confidence: 99%